If it's not what You are looking for type in the equation solver your own equation and let us solve it.
48=6(f+2)
We move all terms to the left:
48-(6(f+2))=0
We calculate terms in parentheses: -(6(f+2)), so:We get rid of parentheses
6(f+2)
We multiply parentheses
6f+12
Back to the equation:
-(6f+12)
-6f-12+48=0
We add all the numbers together, and all the variables
-6f+36=0
We move all terms containing f to the left, all other terms to the right
-6f=-36
f=-36/-6
f=+6
| -4.3-14.5=n | | 6(x-1)/40=3(x+2)/40 | | 90=13+11y | | 12z+23=-109 | | 135=15x-15 | | 2j-2j+10=12 | | 135=15-15x | | X-4(x+1)=x/4-3 | | 4-3(x-2)=7 | | 5x(-5+5)-5+5x=-25 | | 13+3x+17=23+3x | | ‐4x+3x=2 | | 3+19c=-35 | | 8/9m-1/9=5/72 | | 4x+9+9x-6=81 | | x/3+12=22 | | 4x=1.5x+12 | | 3x=2.5x+10 | | 2(2)x-3=-2 | | -16-4x=-8x-8= | | -26-4x=-8x-8= | | 180-(3x-10)=3x-1 | | 8(7-5n)+6n=294 | | Y=11x^2-396 | | 19+2x-18=x+13 | | O.25+15=0.06x+20 | | 13-w=42 | | 3(x-2)^2+81=0 | | 4x-4=-4+2x+18 | | b+(b+45)+90+(2b-90)+1.5=540 | | 9,500+30=500x | | -2(16n-3)-8=82= |